The Small Molecule Ephrin Receptor Inhibitor, GLPG1790, Reduces Renewal Capabilities of Cancer Stem Cells, Showing Anti-Tumour Efficacy on Preclinical Glioblastoma Models - Gravina, Giovanni Luca (Cancers (Basel), 2019)
Therapies against glioblastoma (GBM) show a high percentage of failure associated with the survival of glioma stem cells (GSCs) that repopulate treated tumours. Forced differentiation of GSCs is a promising new approach in cancer treatment. Erythropoietin-producing hepatocellular (Eph) receptors drive tumourigenicity and stemness in GBM. We tested GLPG1790, a first small molecule with inhibition activity versus inhibitor of various Eph receptor kinases, in preclinical GBM models using in vitro and in vivo assays. GLPG1790 rapidly and persistently inhibited Ephrin-A1-mediated phosphorylation of Tyr(588) and Ser(897), completely blocking EphA2 receptor signalling. Similarly, this compound blocks the ephrin B2-mediated EphA3 and EphB4 tyrosine phosphorylation. This resulted in anti-glioma effects. GLPG1790 down-modulated the expression of mesenchymal markers CD44, Sox2, nestin, octamer-binding transcription factor 3/4 (Oct3/4), Nanog, CD90, and CD105, and up-regulated that of glial fibrillary acidic protein (GFAP) and pro-neural/neuronal markers, βIII tubulin, and neurofilaments. GLPG1790 reduced tumour growth in vivo. These effects were larger compared to radiation therapy (RT; U251 and T98G xenografts) and smaller than those of temozolomide (TMZ; U251 and U87MG cell models). By contrast, GLPG1790 showed effects that were higher than Radiotherapy (RT) and similar to Temozolomide (TMZ) in orthotopic U87MG and CSCs-5 models in terms of disease-free survival (DFS) and overall survival (OS). Further experiments were necessary to study possible interactions with radio- and chemotherapy. GLPG1790 demonstrated anti-tumor effects regulating both the differentiative status of Glioma Initiating Cells (GICs) and the quality of tumor microenvironment, translating into efficacy in aggressive GBM mouse models. Significant common molecular targets to radio and chemo therapy supported the combination use of GLPG1790 in ameliorative antiglioma therapy.